Wasyl Tkaczuk – utwory nieznane - Horniatko-Szumiłowicz, Anna (Studia Ukrainica Posnaniensia, 2022)
Aside from 58 novels by Vasyl Tkachuk collected by his daughter, Olga Hoffman, from four published anthologies (Сині чічки, 1935; Золоті дзвінки, 1936; Зимова мельодія, 1938; Весна, 1940) and released by her in a single tome named Сині чічки (2013), twelve works by this forgotten novelist remain entirely unknown to most readers. In-depth analysis confirms that most of them don’t deviate in quality when compared to the works published in Tkachuk’s lifetime, in the aforementioned four anthologies. The novels may be traditional, sometimes even stereotypical in their themes, but at the same time, can surprise the reader when it comes to poetics and stylistics. Despite being conventional stories about village life set in the 1920s and 1930s (according to the 1930s critic Mykhailo Rudnytskyi, these were “humble rural pictures, touching to the core with their simplicity and primitivism”), the rich spectrum of stylistic and linguistic devices present there resulted in them being true gems of Ukrainian literature. Without a doubt, it can be said that these works maintain a form of continuity and thematic-stylistic unity with the anthologized legacy of Vasyl Tkachuk.